Patterns of Downstream Fining on the Lower Chippewa River - Faulkner, Douglas J.; Adams, Hannah R.; Vincent, Allison M. (My University, 2016)
This study examines downstream fning of bed armor on the lower Chippewa River (LCR) in west-central Wisconsin at two different scales: at a river scale and at a local scale of individual armored bars. The upstream limit of our study area is located downstream of the city of Eau Claire where I-94 crosses the Chippewa River and ends approximately 5 km upstream of the city of Durand (60 km). 30 km downstream from the study area the LCR joins the Upper Mississippi River (UMR) (Figure 1). The LCR contains abrupt changes in channel planform morphology. Most notable is an anabranching reach in the middle of the study area. Both upstream and downstream from this reach the river exhibits a single meandering channel planform. Sedimentology changes within the channel are possibly related to the anabranching reach. Changes in channel pattern from reach to reach are moderated by variations in alluvial material and hydrology (Church, 1983).
Color posters with text, images, and graphs.
Keywords: GRADISTAT; Fining; Chippewa River; Posters